Beware too much fine print for study‐abroad experiences. (December 2014) - Porter, Michael
<x xml:space="preserve">Abstract</x> Ships sailing the Mediterranean, classes held in a remote village, Oktoberfest celebrations in Germany, and Machu Picchu explorations led by an archeology professor. These are the images of international travel that entice students to enhance their academic experience through study abroad.